Recognising Facial Surfaces. (November 2013) - Bruce, Vicki; Healey, Patrick; Burton, Mike; Doyle, Tony; Coombes, Anne; Linney, Alf
The extent to which faces depicted as surfaces devoid of pigmentation and with minimal texture cues ('head models') could be matched with photographs (when unfamiliar) and identified (when familiar) was examined in three experiments. The head models were obtained by scanning the three-dimensional surface of the face with a laser, and by displaying the surface measured in this way by using standard computer-aided design techniques. Performance in all tasks was above chance but far from ceiling. Experiment 1 showed that matching of unfamiliar head models with photographs was affected by the resolution with which the surface was displayed, suggesting that subjects based their decisions, at least in part, on three-dimensional surface structure. Matching accuracy was also affected by other factors to do with the viewpoints shown in the head models and test photographs, and the type of lighting used to portray the head model. In experiment 2 further evidence for the importance of the nature of the illumination used was obtained, and it was found that the addition of a hairstyle (not that of the target face) did not facilitate matching. In experiment 3 identification of the head models by colleagues of the people shown was compared with identification of photographs where the hair was concealed and eyes were closed. Head models were identified less well than these photographs, suggesting that the difficulties in their recognition are not solely due to the lack of hair. Women's heads were disproportionately difficult to recognise from the head models. The results are discussed in terms of their implications for the use of such three-dimensional head models in forensic and surgical applications.